A Modified On-Demand Vector Distance Routing Protocol Incorporating Alternate Vehicle-RSU-Vehicle and Vehicle-RSU- RSU Paths - Al-Kasasbeh, Basil (Informatica, 2022)
The Vehicular ad-hoc network (VANET) is an ad-hoc wireless network that allows moving or stationary vehicles to communicate with each other and with the roadside to facilitate various applications, including safety, collision avoidance, and traffic monitoring. The routing protocols provide vehicle-to-vehicle and vehicle-to-roadside communication for the VANET. However, due to the rapid mobility of the vehicles in the network, these protocols suffer from broken links, which leads to unreachable transmission. This paper proposes a new routing protocol based on the ad-hoc on-demand distance vector (AODV) routing protocol to locate the optimal routing of packets in moving vehicles by constructing alternative stable paths with the roadside unit. In the case of the broken links, the alternative stable paths can be used for message transmission, reducing packet discarding. The proposed protocol was simulated, and the results were compared with the original AODV. According to the obtained results, the proposed protocol improves the performance of the AODV in terms of throughput, end-to-end delay, and delivery ratio.